2013
DOI: 10.1186/2047-1440-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of young adults from the UK towards organ donation and transplantation

Abstract: BackgroundThis study examines the attitudes of young British adults towards donating their own organs and those of their family members.MethodsAn opportunity sample of 119 participants (65 female) completed an attitude questionnaire.ResultsMost participants were in favour of donation though substantially fewer had signed up to the organ donation register. A minority of participants was aware of the proposed opt-out system for donation.ConclusionsThe results from this study corroborate and extend previous work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 20 publications
1
27
0
4
Order By: Relevance
“…More negative attitude and refusal of organ donation was reported among Saudi population in Taif (59.3%) and Al-Kharg (75%) by Al-Harthi and Alzahrany (20) and Agrawal et al (21). In west countries, a public survey in the United States revealed that 75% are more likely to donate their organs, and similarly, in the United Kingdom, a crosssectional study included 119 respondents has shown two-thirds of them were in favor of donating their organs and participants who knew someone who had donated or received an organ are having a more positive attitude (22,23). Furthermore, many studies evaluated knowledge and attitude of medical students in different countries such as Saudi Arabia, Ireland, India, and Nigeria revealed adequate level of knowledge, and the majority are willing to donate with a positive correlation between the level of knowledge and the willing toward donation (24)(25)(26).Positive attitude of our study participants was also detected in their preference of who to donate where more than half of them were ready to donate to anyone.…”
Section: Results:-mentioning
confidence: 99%
“…More negative attitude and refusal of organ donation was reported among Saudi population in Taif (59.3%) and Al-Kharg (75%) by Al-Harthi and Alzahrany (20) and Agrawal et al (21). In west countries, a public survey in the United States revealed that 75% are more likely to donate their organs, and similarly, in the United Kingdom, a crosssectional study included 119 respondents has shown two-thirds of them were in favor of donating their organs and participants who knew someone who had donated or received an organ are having a more positive attitude (22,23). Furthermore, many studies evaluated knowledge and attitude of medical students in different countries such as Saudi Arabia, Ireland, India, and Nigeria revealed adequate level of knowledge, and the majority are willing to donate with a positive correlation between the level of knowledge and the willing toward donation (24)(25)(26).Positive attitude of our study participants was also detected in their preference of who to donate where more than half of them were ready to donate to anyone.…”
Section: Results:-mentioning
confidence: 99%
“…On the other hand, a survey conducted on Swiss-Italian young adults reported positive impact of belief in God on their attitude to OD [36]. A report from United Kingdom (UK) stated no significant association between religion and attitude for OD [19]. Some authors reported differential effects among different religious beliefs on the attitude from OD [18].…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have evaluated knowledge and attitude towards OD from various countries but there are few reports from the Middle East area and especially Egypt [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Egypt is an Arab country with a Muslim majority in its population.…”
Section: Introductionmentioning
confidence: 99%
“…In a community of southwestern Ontario, 90% of the respondents cited newspapers or magazines and televisions as their primary sources of information about organ transplantation [20]. A recent study in Venezuela demonstrated that positive media campaign can have a significant impact on organ donation rates [21]. All these studies supported the role of mass media and social media in increasing awareness and the levels of knowledge regarding organ donation worldwide.…”
Section: Discussionmentioning
confidence: 92%